The Effect of Stimulus Policies and Risk-Based Capital Levels on Solvency at PT. Indonesian Takaful using Sharia Principles during the Majeur Force Period (Covid-19 Pandemic) in Indonesia - Nano Suyatna (International Journal of Business, Economics, and Social Development, 2021)
The Covid -19 pandemic is a massive disaster, impacting various sectors of the economy including the Islamic principle insurance sector. The government through the Financial Services Authority (OJK) in dealing with these problems has issued a stimulus policy so that the Islamic principle insurance sector is still able to maintain the level of solvency and risk based capital is maintained. The purpose of this study is to determine the influence of the Stimulus Policy and the level of Risk Based Capital on the level of solvency of sharia-based insurance companies during the Covid-19 Pandemic. The method used is descriptive method with a simple statistical approach. The results show: 1. There is a positive influence of the Stimulus Policy on the Solvency Level of the Islamic principle insurance company sector, 2. There is a positive influence on the Level of Risk Based Capital on the Solvency Level of the Islamic Principle Insurance Company sector, 3. There is an influence of the Stimulus Policy and Level of Risk Based Capital on Simultaneous level of solvency in Islamic principle insurance companies. From the research results, it can be concluded that the Stimulus Policy and Risk Based Capital Level that has been set by the regulator is right on target.